Competitive Fruit and Vegetable Products in Albania - World Bank Group (World Bank, Washington, DC, 2019)
Albania is heavily dependent on its agricultural sector, which accounts for 20.3 percent of GDP, 49 percent of employment and 8.5 percent of total exports. The fruit and vegetable sector represents 20 percent of Albanian agriculture but contributes 36 percent of its exports and this share is expected to increase. The note posits an idea that as the domestic market for many of these products is saturated, Albanian fruits and vegetables have been gaining ground in the Western Balkans and are well positioned to make headway in the EU-28 market as well. However, Albanian producers face many constraints in meeting the rigid and complex demands of the EU market, constraints that an export strategy focused solely on identifying products for export is unlikely to change. The policy paradigm has shifted to approaches that focus on integrating local industries into global value chains that help facilitate technology transfer and create jobs.